Sensitivity of mountain glacier mass balance to changes in bare-ice albedo - Naegeli, Kathrin; Huss, Matthias; id_orcid:0 000-0002-2377-6923 (International Glaciological Society, 2017)
Albedo is an important parameter in the energy balance of bare-ice surfaces and modulates glacier melt rates. The prolongation of the ablation period enforces the albedo feedback and highlights the need for profound knowledge on impacts of bare-ice albedo on glacier mass balance. In this study, we assess the mass balance sensitivity of 12 Swiss glaciers with abundant long-term in-situ data on changes in bare-ice albedo. We use pixel-based bare-ice albedo derived from Landsat 8. A distributed mass-balance model is applied to the period 1997–2016 and experiments are performed to assess the impact of albedo changes on glacier mass balance. Our results indicate that glacier-wide mass-balance sensitivities to changes in bare-ice albedo correlate strongly with mean annual mass balances (r 2 = 0.81). Large alpine glaciers react more sensitively to bare-ice albedo changes due to their ablation areas being situated at lower elevations. We find average sensitivities of glacier-wide mass balance of −0.14 m w.e. a−1 per 0.1 albedo decrease. Although this value is considerably smaller than sensitivity to air temperature change, we stress the importance of the enhanced albedo feedback that will be amplified due to atmospheric warming and a suspected darkening of glacier surface in the near future. ISSN:0260-3055 ISSN:1727-5644